(untitled) (Research, Society and Development, 2020)
The use of Digital Communication Information Technologies (TDIC) can contribute positively to the teaching and learning of Chemistry, due to the difficulties imposed by the decontextualization and abstraction of different contents. Thus, this article aims to map the productions about technologies for teaching chemical concepts, as well as those that address the teaching of Chemical Bonds, and to propose a WebQuest for teaching this content. In this way, the Systematic Literature Review allowed to map the productions from 2008 to 2018. 56 national journals were investigated, with Qualis A1, A2, B1. The results pointed that technological resources most found in the research were software, followed by media and interactive platforms. It is noteworthy that the theme of teacher training was addressed in ten articles; seven contemplated continuing education. The contents found varied between Atomic Models, Periodic Table, Chemical Elements, Organic Chemistry, while only one article covered the contents of Chemical Bonds. Finally, a proposal for teaching Chemical Bonds content was presented, mediated by a WebQuest, followed by a tutorial to contribute to improving the teaching and learning process of this content.